2006
DOI: 10.4321/s1130-01082006000400003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection in the general adult population of the province of Ourense

Abstract: Objectives: to determine the prevalence of Helicobacter pylori infection in the general adult population of the province of Ourense.Material and methods: a cross-sectional study was carried out with a randomly selected populational sample. The diagnosis of Helicobacter pylori infection was reached using the 13 C-urea breath test.Results: three hundred and eighty-three subjects were studied, with a prevalence rate of 69.1% (95% CI: 61.7-75.1%); 69.8% (95% CI: 63.2-76.6%) in males and 68.4% (95% CI: 61.5-75.4%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…However, two studies showed conflicting results. A Spanish study showed less infected individuals in the oldest age groups (>75 years), but these groups consisted of fewer participants . In a Swedish study, the prevalence of H. pylori infection among blood donors was lower after the age of 50 …”
Section: Resultsmentioning
confidence: 96%
“…However, two studies showed conflicting results. A Spanish study showed less infected individuals in the oldest age groups (>75 years), but these groups consisted of fewer participants . In a Swedish study, the prevalence of H. pylori infection among blood donors was lower after the age of 50 …”
Section: Resultsmentioning
confidence: 96%
“…Based on a known sensitivity and specificity for the H. pylori culture of 87% and 100%, respectively, a prevalence of the infection in our area of 70%, and assuming a margin of error of 10% and 95% confidence level, a sample size of 63 cultures was calculated to assess the patterns of antibiotic resistance.…”
Section: Methodsmentioning
confidence: 99%
“…In Spain, H. pylori approximately infects 50% of the population . This prevalence increases up to 70% of the population in the Northwest of Spain …”
Section: Introductionmentioning
confidence: 99%
“…In China, H. pylori prevalence has been reported as high as 83.4% . Additionally, many countries such as China, Japan and Bulgaria have experienced an overall increase in the prevalence of H. pylori infection over the last 20 years (Figure ) . In Canada, the prevalence of H. pylori is approximately 30%; however, within the Aboriginal populations living in Canada, the prevalence of H. pylori has been reported as high as 95% .…”
Section: Prevalence Of H Pylori Infectionmentioning
confidence: 99%